APPLICATION OF MODERN INFORMATION TECHNOLOGIES OF LEARNING IN CONDITIONS OF TRANSFORMATION OF MODERN SOCIETY (Spectrum Journal of Innovation, Reforms and Development, 2022)
The article discusses the role and importance of the scientific and technical equipment of the educational process in order to obtain a quality competitive education. Only a comprehensive, connected by a single didactic concept, the use of an organizational and planning system will increase the effectiveness of computer training in the system of professional training of specialists.